Keefektifan Metode Pembelajaran Peer Tutoring terhadap Keterampilan Menulis Teks Cerpen Siswa Kelas XI IPA 3 SMA Negeri 2 Gowa - Ananda Reski Novalia; Muhammad Saleh; Azis Azis (SOCIETIES: Journal of Social Sciences and Humanities, 2022)
Abstract: This study aims to (1) determine the differences in the short story writing skills of students in class XI IPA 3 SMA Negeri 2 Gowa before and after using the peer tutoring learning method (2) prove the effectiveness of the use of peer tutoring learning methods on the short story writing skills of students in class XI IPA 3 SMA Negeri 2 Gowa. The type of research used in this research is experimental research "One Group Pretest - Posttest Design". Data collection techniques used in this study were tests, observations, and documentation. The collected data were analyzed using descriptive statistics analysis and inferential statistics analysis. The results of this study indicate that the students' short story writing skills in the pretest obtained an average score of 64.68 and were in the less category with a frequency of 25 students (78.12%). Then it increased in the posttest which obtained an average score of 82.96 and was in the good category with a frequency of 18 students (56.25%). The results of the t-test in this study also showed a significance value (2 tailed) or p-value smaller than the significance level (0.000 < 0.05), then Ho was rejected and Ha was accepted. Based on the results of the study, it can be concluded that there is a difference in the average value of short story writing skills for students of class XI IPA 3 SMA Negeri 2 Gowa before and after using the peer tutoring learning method and the peer tutoring learning method was effectively used for the short story writing skills of students of class XI IPA 3 SMA Negeri 2 Gowa. Keywords: Effectiveness, Peer Tutoring Method, Short Story